The Impact of Organizational Culture on Non-Financial Performance: A Mediation Effect of Sustainability Balanced Scorecard Measurements - Alsawayeh, Ali Mohamed; Sukoharsono, Eko Ganis; Hariadi, Bambang (Accounting Department,, 2023)
Purpose—This research aims to illuminate the non-financial performance level in the hotel industry in East Java cities in Indonesia. That is, it aims to analyze the impact of organizational culture on non-financial performance by investigating the effectiveness of using Sustainability Balanced Scorecard (SBSC) measurements in assessing the relation between organizational culture and non-financial performance. Design/methodology/approach — This exploratory research examines a sample of 65 hotels operating in different targeted markets. In order to have a better understanding and provide a clear discussion related to these relationships in sufficient depth, the theoretical framework of this research has been designed and developed based on a wide review of relevant research, theories, and findings. The developed research framework adopts the mixed form of the contingency of fit (selection and mediating-based interaction approaches) to investigate the contingency relationship. The survey questionnaire is distributed using an offline approach. Therefore, the collected data is analyzed by using the Partial Least Square Path Modelling (PLS-PM) method along with taking advantage of SmartPLS 3.0 Software. Findings — The findings indicated that organizational culture (Clan, Adhocracy, Market, and Hierarchy) has a positive and significant influence on the effective implementations and usage of Sustainability Balanced Scorecard Measurements, namely, financial, internal business process, customer, learning and growth, environmental, and community. These five perspectives of SBSC have a mediation-interaction relationship between the impact of organizational culture and the organizational non-financial performance levels. Therefore, SBSC measurements significantly and positively influence non-financial performance (product/ quality service level, customer satisfaction level, employee loyalty level, and social sustainability level). Practical implications—This research contributes empirically to the existing literature related to management accounting practices, and more particularly, evaluation and performance practices, by providing findings from developing countries and focusing on the SBSC’ measurements’ usage at hotel businesses operating in three cities in East Java. Originality/value — The multiple evaluations and performance measurements of BSCS proved to be innovative business measurements to enhance the decision-making process and improve a business organization's overall value and performance. Thus, this research paper adopts the contingency model to determine the main internal contingency factor that explains the extent of SBSC measurements’ usage and the effective influence of SBSC measurements on non-financial performance levels. Keywords — Organizational Culture, Non-Financial Performance, Sustainability Balanced Scorecard’s Measurements, Hotel Industry, East Java, Indonesia. Paper type — Exploratory Research